INTEGRATION OF MULTIMODAL LITERACY WITH A DEEP LEARNING APPROACH TOWARDS ELEMENTARY SCHOOL STUDENTS' READING COMPREHENSION: A CASE STUDY - Amalia Anisa Fitri; Suci Herwani (Universitas Majalengka, 2026)
This study aims to analyze the integration of multimodal literacy based on immersive learning in elementary school students' reading comprehension and its relationship to reading comprehension skills. Although multimodal literacy has been widely researched, studies that integrate it with an immersive learning approach in the elementary school context are still limited, particularly in examining students' meaning construction processes at the inferential and reflective levels. This study used a qualitative approach with a case study design conducted at SDN 04 Karangbener with one fourth-grade teacher and 17 fourth-grade students as subjects. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using the Miles and Huberman model through the stages of data reduction, data presentation, and drawing conclusions with a thematic coding process. The results showed that the integration of video as an initial stimulus and digital text as a reinforcement of understanding was able to increase student engagement and facilitate cognitive integration between representations, so that understanding develops from the literal to the inferential and reflective levels as part of the immersive learning process. However, the implementation of learning still faces obstacles such as limited time, digital resources, and differences in student abilities. Theoretically, this research contributes to strengthening the integration of multimodal literacy and deep learning as a pedagogical framework in reading learning, while practically it shows that its effectiveness depends on the readiness of the learning environment and teacher competence.